2017
DOI: 10.1089/dna.2016.3463
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Media-Induced Renal Inflammation Is Mediated Through HMGB1 and Its Receptors in Human Tubular Cells

Abstract: With the rapid development of imaging diagnosis and interventional therapy, contrast media (CM) are widely used in clinics. However, contrast-induced nephropathy (CIN) is the third leading cause of hospital-acquired acute renal failure accounting for 10-12% of all causes of hospital-acquired renal failure. Recent study found that inflammation may participate in the pathogenesis of CIN, but the role of it remains unclear. HK-2 cells were treated with Iohexol, Urografin, and mannitol. Two types of CM increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…7,8,13 HMGB1 is also thought to be involved in the development of PC-AKI as increased levels of HMGB1 were found in the supernatants of previous cell experiments after cells were exposed to contrast media. 14 These results were comparable to our animal study which also found increased serum HMGB1 in the PC-AKI group. We also showed that total cellular HMGB1 as well as cytoplasmic and serum HMGB1 increases after the administration of contrast media, suggesting that HMGB1 might be actively translocated from the nucleus to the cytoplasm after contrast media exposure.…”
Section: Discussionsupporting
confidence: 90%
“…7,8,13 HMGB1 is also thought to be involved in the development of PC-AKI as increased levels of HMGB1 were found in the supernatants of previous cell experiments after cells were exposed to contrast media. 14 These results were comparable to our animal study which also found increased serum HMGB1 in the PC-AKI group. We also showed that total cellular HMGB1 as well as cytoplasmic and serum HMGB1 increases after the administration of contrast media, suggesting that HMGB1 might be actively translocated from the nucleus to the cytoplasm after contrast media exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported that CIN is a complex pathological process related to multiple pathological cascades. Oxidative stress [6,7], renal ischemia [8], endothelial dysfunction [9], inflammation [10,11], apoptosis [12][13][14], and tubular transport dysfunction [15] may be involved in the pathogenesis of CIN. Increasing studies point out that reactive oxygen species (ROS) play the key role in CIN development [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiological mechanism of CIN is complex and not clear, it is assumed that contrast-mediated renal vasoconstriction, renal ischemia, inflammatory response, and oxidative stress are significant components. 8 11 Nicorandil is composed of nicotinamide vitamins and organic nitrates. It is an adenosine triphosphate (ATP)-sensitive potassium channel opener and is often used to prevent slow coronary flow or no flow.…”
Section: Introductionmentioning
confidence: 99%